Diagnosis and treatment of tuberculosis in adults with HIV. Issue 35 (2nd September 2022) - Yang, Qiaoli; Han, Jinjin; Shen, Jingjing; Peng, Xinsen; Zhou, Lurong; Yin, Xuejing
Abstract : Mycobacterium tuberculosis, the causative agent of tuberculosis (TB), continues to pose a major public health problem and is the leading cause of mortality in people infected with human immunodeficiency virus (HIV). HIV infection greatly increases the risk of developing TB even before CD4+ T-cell counts decrease. Co-infection provides reciprocal advantages to both pathogens and leads to acceleration of both diseases. In HIV-coinfected persons, the diagnosis and treatment of tuberculosis are particularly challenging. Intensifying integration of HIV and tuberculosis control programmes has an impact on reducing diagnostic delays, increasing early case detection, providing prompt treatment onset, and ultimately reducing transmission. In this Review, we describe our current understanding of how these two pathogens interact with each other, new sensitive rapid assays for TB, several new prevention methods, new drugs and regimens.